2015
DOI: 10.1007/s13277-015-3890-4
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of quercetin in autophagy and apoptosis in HeLa cells

Abstract: In recent years, the effects of quercetin on autophagy and apoptosis of cancer cells have been widely reported, while effects on HeLa cells are still unclear. Here, HeLa cells were subjected to quercetin treatment, and then proliferation, apoptosis, and autophagy were evaluated using MTT, flow cytometry, and MDC staining, respectively. The LC3-I/II, Beclin 1, active caspase-3, and S6K1 phosphorylation were detected using Western blot assay. The ultrastructure of HeLa was observed via transmission electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 12 publications
(12 reference statements)
3
22
0
Order By: Relevance
“…The current study revealed decreased Beclin‐1 level in rotenone‐treated group indicating suppression of autophagy as previously observed , whereas quercetin co‐treatment increased it, suggesting induction of autophagy which came in line with previous reports demonstrating that quercetin upregulated Beclin‐1 expression .…”
Section: Discussionsupporting
confidence: 92%
“…The current study revealed decreased Beclin‐1 level in rotenone‐treated group indicating suppression of autophagy as previously observed , whereas quercetin co‐treatment increased it, suggesting induction of autophagy which came in line with previous reports demonstrating that quercetin upregulated Beclin‐1 expression .…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that quercetin can induce autophagy in gastric cancer cells and HeLa cells 24 25 . Autophagy is the process by which cellular components can be recycled, either as a normal process or to remove damaged organelles 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Wortmannin negates the protective effect of quercetin, indicating that the protection operates through the increase in autophagy, as we know that autophagy induced by several means including by rapamycin can protect cells against CPT [19]. Quercetin induces protective autophagy in gastric cancer cells and HeLa cells, while disruption of autophagy by genetic knockout or blockage of autophagy by 3-methyladenine or chloroquine induced apoptosis in these cells [39,40]. Quercetin also induces autophagy through ER stress in ovarian cancer cells [41].…”
Section: Discussionmentioning
confidence: 99%